The Role of Broccoli ( Brassica oleracea ) in Treatment For Induced Polycystic ovary syndrome in Albino rats ( Rattus norvegicus ) - J. AL-Shahery, Nahla; A. Salih, Roqaya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The goal of present study was to investigate the benefits of broccoli (as antiandrogenic plant) in protection and treatment for reproductive hormonal and metabolic disturbance, which combined with polycystic ovarian syndrome (PCOS). The PCOS model was introduced by injecting subcutaneously prepubertal female rats at 21 days old with Letrozole for 39 days, and divided into 6 groups (8 rats each ) as follows: Group 1: Female rats were injected with 0.1 ml of normal saline. Group 2: Female rats were injected with 0.1 ml of 400 µg Letrozole Group 3: Female rats were injected with 0.1 ml of 400 µg L with orally gavaged of broccoli juice. Group 4: Female rats were injected with 0.1 ml of normal saline and at the end of the last injection were orally gavaged with destil water for 30 days . Group 5: Female rats were injected with 0.1 ml of 400 µg L and at the end of the last injection were orally gavaged with destil water for 30 days. Group 6: Female rats were injected with 0.1 ml of 400 µg L and at the end of the last injection were orally gavaged with broccoli juice for 30 days. Females of all groups were sacrificed after 24 hours from last treatment to undertake study on weight, histological, hormonal and metabolic for each group. All L- treated rats showed reproductive hormonal and metabolic symptoms of PCOS. Also a well improvement has been noticed in all syndrome symptoms on females gavaged with broccoli juice. These results indicate that broccoli juice has got a protective and curative role against this syndrome.